2017
DOI: 10.1155/2017/6038641
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Awake Glioma Surgery in “Critical” Language Areas on Cognition: 4 Case Studies

Abstract: Awake surgery with electrocorticosubcortical stimulation is the golden standard treatment for gliomas in eloquent areas. Preoperatively, mostly mild cognitive disturbances are observed with postoperative deterioration. We describe pre- and postoperative profiles of 4 patients (P1–P4) with gliomas in “critical” language areas (“Broca,” “Wernicke,” and the arcuate fasciculus) undergoing awake surgery to get insight into the underlying mechanism of neuroplasticity. Neuropsychological examination was carried out p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The majority of the reviewed fMRI studies [45, 46, 52] failed to identify statistically significant differences in motor and language activations just because only few patients have been studied by means of two fMRI examinations. In the literature, overall, the majority of studies described cortical plasticity only in small patients' samples or single cases [12, 54], but substantial evidence derived from the analysis of more consistent samples is still lacking. Recruitment of a large and homogenous sample of glioma patients in a prospective protocol can be challenging, due to the large heterogeneity of patients' characteristics and tumor-related features, i.e., age at the diagnosis, clinical and cognitive impairments, tumor location, tumor grade, and clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the reviewed fMRI studies [45, 46, 52] failed to identify statistically significant differences in motor and language activations just because only few patients have been studied by means of two fMRI examinations. In the literature, overall, the majority of studies described cortical plasticity only in small patients' samples or single cases [12, 54], but substantial evidence derived from the analysis of more consistent samples is still lacking. Recruitment of a large and homogenous sample of glioma patients in a prospective protocol can be challenging, due to the large heterogeneity of patients' characteristics and tumor-related features, i.e., age at the diagnosis, clinical and cognitive impairments, tumor location, tumor grade, and clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lower grade infiltrating gliomas are characterized by progressive functional reshaping, due to their slow growth. Such modifications can occur during the natural history of illness or following a treatment [12, 13]. However, the exact mechanisms underlying brain cortical plasticity remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Second surgery for recurrent HGG and LGG has been shown to be possible without significant cognitive damage in the months after surgery ( 109 ). Other studies have found a mixed picture of some patients experiencing cognitive improvement and others in the same study who experience cognitive decline or no change ( 39 , 58 , 60 , 76 , 110 – 113 ), or improvements in some cognitive domains and deterioration ( 2 ) or no change ( 46 ) in others; such a pattern could indicate ‘noise’ within the cognitive data. The cognitive domain being tested is important, as shown by one study where a decline in most cognitive domains was observed 5 days after surgery compared to pre-operatively, but only memory remained impaired 1 month after surgery ( 91 ).…”
Section: Resultsmentioning
confidence: 85%
“…There is wide variability in language localization between individuals ( 75 ), which means that a tumor located in a specific anatomical location may have different effects across the population. This may explain why not all patients with tumors in areas of the brain deemed ‘critical’ for language have cognitive disturbance ( 76 ). Other factors that influence study results have been identified; for example, in a study of 20 adult LGG patients who underwent tests of writing fluency and oral lexical retrieval, typing speed accounted for some of the differences observed between the LGG patients preoperatively and a reference group of 31 individuals without neurological disease ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they might allow for a higher amount of large-scale functional reorganization by activating latent functional parts of the larger language network (e.g., Duffau et al, 2003 , Krishna et al, 2021 , Traut et al, 2019 ). This is supported by the fact that low-grade glioma patients often show little or no functional impairment at the time of diagnosis (e.g., Gil-Robles et al, 2008 , Mandonnet et al, 2003 , Satoer et al, 2017 ). In contrast, high-grade gliomas, which grow faster, tend to cause more severe and earlier impairment ( Bizzi et al, 2012 , Campanella et al, 2009 , Noll et al, 2015 , Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 96%